2015
DOI: 10.1017/jfm.2015.59
|View full text |Cite
|
Sign up to set email alerts
|

A simple and practical model for combined wave–current canopy flows

Abstract: Laboratory experiments were used to evaluate and improve modelling of combined wave-current flow through submerged aquatic canopies. Horizontal in-canopy particle image velocimetry (PIV) and wavemaker-measurement synchronization allowed direct volume averaging and ensemble averaging by wave phase, which were used to fully resolve the volume-averaged unsteady momentum budget. Parameterizations for the drag, Reynolds stress, vertical advection, wake production and shear production were tested against the laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 43 publications
2
50
0
Order By: Relevance
“…Moreover, the present model has no explicit accommodations for wave‐current and flow‐element interactions. Both these mechanisms have been shown to have considerable influence over mean canopy hydrodynamics (Luhar and Nepf ; Zeller et al ; Zeller et al). Although the experiments in this study were not designed to account for these interactions, their investigation—especially in such complex conditions—should be kept as a top priority.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the present model has no explicit accommodations for wave‐current and flow‐element interactions. Both these mechanisms have been shown to have considerable influence over mean canopy hydrodynamics (Luhar and Nepf ; Zeller et al ; Zeller et al). Although the experiments in this study were not designed to account for these interactions, their investigation—especially in such complex conditions—should be kept as a top priority.…”
Section: Resultsmentioning
confidence: 99%
“…Data processing schemes like the one described above are unable to overcome the fundamental challenge of data paucity. For that, we have begun a transition toward data collection via particle image velocimetry, an approach that yields far richer velocity field information (Weitzman et al ; Zeller et al ; Zeller et al). This will allow us to characterize the horizontal variability of flow statistics and develop new methods for interpreting sparse measurements…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory experiments with idealized canopies [e.g., Lowe et al ., ; Luhar et al ., ] and field experiments in seagrass canopies [e.g., Infantes et al ., ] have demonstrated that the attenuation of the root‐mean‐squared (RMS) wave orbital velocities within the canopy is always less than that of a unidirectional flow of equivalent magnitude. This is due to the wave‐driven oscillatory pressure gradient, which is opposed by both canopy drag and inertial forces [e.g., Lowe et al ., ; Zeller et al ., ]. Furthermore, wave phase‐dependent Reynolds stresses are enhanced near the top of the roughness and then decrease toward zero within the canopy before they increase again near the bed [e.g., Lowe et al ., ; Luhar et al ., ].…”
Section: Background: Flow Structure and Sediment Transport Within Roumentioning
confidence: 99%
“…The dynamics of wave‐current interactions that occur within large roughness (canopies) are still not well‐established. However, it is reasonable to assume that the drag imposed by large roughness elements will cause greater attenuation of the current‐component of the flow relative to the wave‐component, which is supported by experimental observations [e.g., Lowe et al ., ; Zeller et al ., ]. Thus, under wave‐current conditions the flow within the roughness should be more strongly influenced by the contribution of the waves than the current.…”
Section: Background: Flow Structure and Sediment Transport Within Roumentioning
confidence: 99%
“…Meanwhile, the wave‐driven currents and wave asymmetry also influence the asymmetry of blade motion. It is therefore worthwhile not only to investigate the dynamics of vegetation, but to also incorporate the two‐way feedback between the asymmetric blade motion and the wave flow field in wave‐vegetation models, such as the coupled CFD and immersed boundary method model by Chen and Zou () and N‐box model (Zeller et al, ). Improved blade posture simulations by the present consistent‐mass cable model will yield more accurate predictions for wave‐vegetation interaction.…”
Section: Discussionmentioning
confidence: 99%